ENSO‐Driven Variability in Ozone Sources and Its Impact on Tropospheric Ozone Radiative Forcing - Arman Pouyaei; Paul Ginoux; Vaishali Naik; Jing Feng; Larry W. Horowitz; Fabien Paulot (Geophysical Research Letters)
Abstract Ozone is the third strongest anthropogenic greenhouse gas with highest radiative efficiency in the tropical upper troposphere. Variability driven by El Niño‐Southern Oscillation (ENSO) modulates tropospheric column ozone instantaneous radiative forcing (TCO‐IRF) through changes in atmospheric dynamics, natural emissions, and stratospheric‐tropospheric exchange in the tropics. Using the Geophysical Fluid Dynamics Laboratory Atmospheric Model v4.1, which includes detailed ozone chemistry, we analyze the impacts of drivers on the ozone profile associated with El Niño and La Niña events between 2004 and 2019. Findings show that alongside ENSO‐driven atmospheric circulation changes, lightning‐induced nitrogen oxide over Atlantic and Pacific oceans, subtropical stratospheric intrusions, and biomass burning in equatorial Asia significantly impact TCO‐IRF in the tropics. Additionally, radiative effects from tropical tropospheric ozone increase by up to 0.03 Wm−2 during La Niña seasons and weaken by 0.02 Wm−2 in El Niño seasons, highlighting the importance of assessing ENSO‐driven TCO‐IRF variability for understanding future climate.